Prediksi Permintaan Kantong Darah Berdasarkan Golongan Darah Menggunakan Metode Single Moving Average (SMA) - Isran Mertosono; Yasin Mustofa (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2022)
Blood donation is blood taking process from any volunteer to store in a blood bank for blood transfusion purposes. Blood donation is usually conducted routinely at the Blood Transfusion Unit. The demand for blood is estimated to be higher due to the rapid development of medical science. The rapid development of medical science requires a lot of blood needs, one of which is in organ transplant procedures. The prediction system for blood bag demand can be developed using the Single Moving Average method. The Moving Average method is suitable for long-term data. A single moving average is a forecast for a future period that requires historical data over a certain period. The level of accuracy in predicting blood demand is categorized as quite Good, with an accuracy rate of 75% with MAPE testing of 25%. The accuracy results show that the application designed is feasible to predict the demand for blood bags by adding the amount of data that can optimize the Single Moving Average method to produce more precise and accurate predictions.Keywords: Single Moving Average (SMA), blood demand prediction, MAPE